Tantangan Pengelola Keuangan Negara Di Era Digital - Putri, Aliyah; Shesaria, Nazwa; Tauhid, Imam (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
This article discusses the challenges faced by state financial managers in the digital era, especially in adopting digital technology to increase the efficiency, transparency, and accountability of public financial management. In this era, the use of technology such as big data, artificial intelligence (AI), and blockchain opens up great opportunities for the government to improve the quality of public services and budget and revenue management. However, on the other hand, state financial managers are faced with various challenges, including data security issues, privacy risks, limited human resources skilled in digital technology, and the complexity of regulations that have not fully accommodated technological developments. This article highlights the importance of policy adaptation, strengthening regulation, and increasing human resource capacity as the main strategy to face these challenges. The results of the study show that the success of state financial management in the digital era is highly dependent on the government's ability to balance technological innovation with good governance and a strict monitoring system. Keywords: State financial management, digital technology, big data, blockchain